A calculus problem by أحمد الحلاق

Calculus Level 4

lim x 1 x + 3 x + 7 3 3 x 2 4 4 x 1 \large \lim_{x\to 1} \dfrac{\sqrt{x+3} \sqrt[3]{x+7} \sqrt[4]{3x-2} - 4}{x-1}

The limit above has a closed form. Find the value of this closed form.

Give your answer to 3 decimal places.


The answer is 3.667.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

L = lim x 1 x + 3 x + 7 3 3 x 2 4 4 x 1 This is a 0/0 case, so L’H o ˆ pital’s rule applies. = lim x 1 1 2 ( x + 3 ) 1 2 ( x + 7 ) 1 3 ( 3 x 2 ) 1 4 + 1 3 ( x + 3 ) 1 2 ( x + 7 ) 2 3 ( 3 x 2 ) 1 4 + 3 4 ( x + 3 ) 1 2 ( x + 7 ) 1 3 ( 3 x 2 ) 3 4 1 = 1 2 1 2 2 1 + 1 3 2 1 4 1 + 3 4 2 2 1 = 1 2 + 1 6 + 3 = 11 3 3.667 \begin{aligned} L & = \lim_{x \to 1} \frac {\sqrt{x+3}\sqrt[3]{x+7}\sqrt[4]{3x-2}-4}{x-1} \quad \quad \small \color{#3D99F6}{\text{This is a 0/0 case, so L'Hôpital's rule applies.}} \\ & = \lim_{x \to 1} \frac {\frac 12 (x+3)^{-\frac 12} (x+7)^\frac 13 (3x-2)^\frac 14 + \frac 13 (x+3)^\frac 12 (x+7)^{-\frac 23} (3x-2)^\frac 14 + \frac 34 (x+3)^\frac 12 (x+7)^\frac 13 (3x-2)^{-\frac 34}}{1} \\ & = \frac 12 \cdot \frac 12 \cdot 2 \cdot 1 + \frac 13 \cdot 2 \cdot \frac 14 \cdot 1 + \frac 34 \cdot 2 \cdot 2 \cdot 1 \\ & = \frac 12 + \frac 16 + 3 = \frac {11}3 \approx \boxed{3.667} \end{aligned}

I Almost used the same approach , but i like it this way .... \text{I Almost used the same approach , but i like it this way .... }

Let \small \text{Let } f ( x ) = ( x + 3 ) 1 2 ( x + 7 ) 1 3 ( 3 x 2 ) 1 4 f(x)=(x+3)^{\frac12}(x+7)^{\frac13}(3x-2)^{\frac14}

L = lim x 1 f ( x ) 4 x 1 Apply L’Hopitals Rule L = lim x 1 f ( x ) = f ( 1 ) L = \displaystyle\lim_{x \to 1} \dfrac{f(x)-4}{x-1} \quad \quad \small\color{#3D99F6}{\text{Apply L'Hopitals Rule}} \\ L=\displaystyle\lim_{x \to 1} f^{'}(x) = f^{'}(1) \\

Now, Take Log on both sides of our Original Function . We get \text{Now, Take Log on both sides of our Original Function . We get }

ln [ f ( x ) ] = 1 2 log ( x + 3 ) + 1 3 log ( x + 7 ) + 1 4 log ( 3 x 2 ) \ln{[f(x)]}= \dfrac{1}{2}\cdot\log{(x+3)}+\dfrac{1}{3}\cdot\log{(x+7)}+\dfrac{1}{4}\cdot\log{(3x-2)}

Differentiate Both sides w.r.t x \text{Differentiate Both sides w.r.t } x

f ( x ) = f ( x ) ( 1 2 x + 6 + 1 3 x + 21 + 3 12 x 8 ) L = f ( 1 ) = f ( 1 ) ( 1 8 + 1 24 + 3 4 ) L = 1 2 + 1 6 + 3 = 11 3 f^{'}(x)=f(x)\left( \dfrac{1}{2x+6}+\dfrac{1}{3x+21}+\dfrac{3}{12x-8} \right) \\ L=f^{'}(1)=f(1)\left( \dfrac{1}{8}+\dfrac{1}{24}+\dfrac{3}{4} \right) \implies L=\dfrac{1}{2}+\dfrac{1}{6}+3 = \boxed{\dfrac{11}{3}}

Sabhrant Sachan - 4 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...